Analysis of the Influence of System QuaAnalysis of the Influence of System Quality, Information Quality, and Service Quality on User Satisfaction of Payment Systems Using Virtual Accountslity, Information Quality, and Service Quality on User Satisfaction of Payment Systems Using Virtual Accounts - Azrul Azmani; Tutik Lestari; Muhammad Dzakky Ikhwani Imaduddin; Ajinarasena Hermanu; Gandung Triyono (JURNAL SISFOTEK GLOBAL, 2026)
This study aims to analyze the influence of system quality, information quality, and service quality on user satisfaction in virtual account payment systems implemented at Pesantren Darunnajah. The increasing adoption of digital payment solutions in educational institutions underscores the need for reliable systems that ensure convenience, security, and efficiency. Using the Technology Acceptance Model (TAM) as a theoretical framework, data were collected through a survey of 36 respondents, including guardians and staff, and analyzed using multiple linear regression. The findings reveal that system quality, information quality, and service quality all have a significant positive effect on user satisfaction, with service quality emerging as the most influential factor. These results highlight the importance of responsive support and accurate information in enhancing user experience. The study contributes to the literature on digital payment adoption in Islamic educational institutions and provides practical insights for improving service delivery. Future research should explore additional factors such as security, interface design, and user trust to broaden understanding of technology acceptance in similar contexts.